Biodiversity Studies on Oscillatoriaceae form Jalgaon Nala of Ashti Taluka in Beed District, India - S.K. Jogdand1, S.M. Talekar1*, M.J. Jadhav2, (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: medium none; padding-left: 0in; background: white; padding-bottom: 1pt; border-left: medium none; padding-top: 0in; border-bottom: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> A Critical study has been made on biodiversitical studies of oscillatoiriaceae (cyanophyceae) in Jalgaon Nala of Ashti Taluka in Beed district during the period form June 2007 to May 2009. Algal samples were collected at monthly interval form five sites of Jalgaon Nala during the period of investigation. Microphotograph and line drawings of algal taxa were made by Digital camera and camera lucida. Algal taxa of cyanophyceae were indetified with the help of standard monographs and recent literature. In present study oscillatoriaceae included six genera. Viz Arthrospira Spirulina,Â  Oscillatoria, Phormidium, Lyngbya, and Mircocoleus were recorded. A total 33 algal taxa of oscillatoriaceae were recorded in present biodeversitical study. Among 33 algal taxa species of oscillatoria are dominant compared to other taxa. 1P.G. Department of Botany, Mrs.K.S.K. College Beed- 431122 (M.S.), India; 2Department of Botany, Sir Sayyed College, Aurangabad, India * Corresponding Author, Email: ram_mango@yahoo.com Please Cite This Article As: S.M. Talekar, M.J. Jadhav, S.K. Jogdand . 2010. Biodiversity Studies on Oscillatoriaceae form Jalgaon Nala of Ashti Taluka in Beed District, India. J. Exp. Sci. 1(2): 03-04.